From investing to saving in education : principals and educational savings - Elsilä, Laura (2017)
In autumn 2015, it was announced that the government would execute massive budget cuts to education. This was due to the efforts of the new government to save money and balance the state economics. The amount of money that the state intended to save from the basic education, also known as primary and lower secondary schools nationwide was estimated to be around 40 million euros. 30 million euros out 40 million euro savings was from group size money and 10 million of development money. Money directed to group sizes has been used by the schools to downsize the class and group sizes. The developing money on the other hand is for the development of the schools, for example to modernize equipment and learning spaces. The topic of this research is the savings done from education in the context of changed educational politics and legally mandated tasks the school have. This study asked from the principals their views about these educational budget cuts and how they see those to affect to schools. The research questions the most worrying aspects of saving from basic education and how the principals see diminishing resources to affect to their school. Second research question was the future Finnish basic education and how the principals viewed that. The research was conducted as qualitative research where the principals were interviewed and their answers to the interview question were analyzed with content analysis. In the interviews, the question were in specific order and the question were asked in same order from every participating principal. Research questions were answered during the interviews so the findings are written down as principals answered to the question. These findings suggest that principals are concerned about the growth of the group and class sizes, the work load of their teachers, the quality of teaching and the diminishing resources to organize support service in schools. When asked about the future of the Finnish basic education in general the principals were positive and faith to the future of the basic education.